1983
DOI: 10.1063/1.444479
|View full text |Cite
|
Sign up to set email alerts
|

Ordered structure in dilute solutions of highly charged polymer lattices as studied by microscopy. I. Interparticle distance as a function of latex concentration

Abstract: The coexistence of ordered and disordered regions has been observed in dilute solutions of highly charged monodisperse latex particles, a copolymer of styrene and styrenesulfonate, by using a metallurgical microscope. Unlike latex particles of low charge numbers, the interparticle distances (2Dexp) in the hexagonal ordered regions are smaller than the calculated average values for a face-centered-cubic distribution (2D0,h) at low polymer concentrations (0.2–2 vol %). However, at high concentrations, up to 12%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 32 publications
10
68
0
Order By: Relevance
“…(53) is very close to the (largest) salt-free saturation (Z → ∞) effective charge θ sat = 3Z sat ℓ B /a ≈ 45 determined by Alexander et al 24 It has been speculated 15 that this curious coincidence drives suspensions of highly charged colloids close to criticality. This might account for some of the experimental findings in dilute deionized aqueous suspensions of highly charged colloids, 41,42,43 which then would be explained by the presence of strong density fluctuations near the criticality. 15 Another consequence that effective charges are below the saturation value, and therefore also below the linearized critical threshold, is that charge renormalization would stabilize the suspension against phase separation, because the unstable region predicted by linearized theory is unreachable (or at least drastically reduced) when including renormalized effective charges.…”
Section: In the Presence Of Neutralizing Counterions And Added Salt (mentioning
confidence: 99%
“…(53) is very close to the (largest) salt-free saturation (Z → ∞) effective charge θ sat = 3Z sat ℓ B /a ≈ 45 determined by Alexander et al 24 It has been speculated 15 that this curious coincidence drives suspensions of highly charged colloids close to criticality. This might account for some of the experimental findings in dilute deionized aqueous suspensions of highly charged colloids, 41,42,43 which then would be explained by the presence of strong density fluctuations near the criticality. 15 Another consequence that effective charges are below the saturation value, and therefore also below the linearized critical threshold, is that charge renormalization would stabilize the suspension against phase separation, because the unstable region predicted by linearized theory is unreachable (or at least drastically reduced) when including renormalized effective charges.…”
Section: In the Presence Of Neutralizing Counterions And Added Salt (mentioning
confidence: 99%
“…. N), have a radius a, a fixed charge −Ze, and hence a surface charge density σ C = Z/4πa 2 . We assume that the suspension is in osmotic equilibrium with a reservoir of monovalent point charges ±e of total density 2n …”
mentioning
confidence: 99%
“…In the homogeneous limit this gives a charge densityỹ for the stripes plus the side strips via Eqs. (13) and (15). The average charge densityȳ on the original stripe follows by assigning the charge density to a smaller surface,ȳ =ỹ(D 1 + 2s)/D 1 .…”
Section: B Analytical Approximationmentioning
confidence: 99%
“…Ion-ion correlations, which are ignored in the mean-field-type Poisson-Boltzmann (PB) theory, might be an explanation for these observed attractions in the case of multivalent ions. [8][9][10][11][12][13][14] However, evidence for electrostatic attractions has also been reported for suspensions with only monovalent ions, [15][16][17][18] causing heated debates in the literature on the breakdown of the classic DLVO theory due to many-body effects, the vicinity of glass walls, hydrodynamic forces, etc. Interestingly, it has also been suggested that charge inhomogeneities can be responsible for these attractions, [19][20][21][22][23] where the heterogeneity of the surface charge may be due to an incidentally present or purposely designed underlying chemical structure, or by clustering of adsorbed surfactants.…”
Section: Introductionmentioning
confidence: 99%